The Memorial Space of the "Desaparecidos. Some epistemological perspectives (Teología, 2016)
The question that guides this work is referred to the possibility of extracting some epistemological perspectives of the production of a memorial space. Its theme is related to the ways of developing the social trauma. Historical time to which it refers is the last civic-military dictatorship (March 1976- December 1983). The route of this contribution has three parts. In the first, we consider the notions of body and narration; the second presents outlines of answers to the question posed, and the third is briefly referred to two European and Christian women: Alice Domon (France, 1937- Argentina, 1977) and Elisabeth KÁ¤semann (Germany, 1947- Argentina, 1977). Both lived in Latin America and can be considered true humanitarian spaces of peace.
Keywords: Disappeared in Argentina; Body; Narration; Epistemology; Peace